PENGARUH KARAKTERISTIK INDIVIDU DAN PENGEMBANGAN KARIR TERHADAP KINERJA PEGAWAI - Hadi Wahyudi; Murdjani Kamaluddin; Sinarwati Sinarwati (Pascasarjana Universitas Halu Oleo, 2017)
The purpose of this study were (1) To determine the effect of individual characteristics and career development on the performance of staff at the Board of Social Empowerment and Rural Government of Southeast Sulawesi. (2) To determine the effect of individual characteristics on the performance of staff at the Board of Social Empowerment and Rural Government of Southeast Sulawesi. (3) To determine the effect of career development on the performance of staff at the Board of Social Empowerment and Rural Government of Southeast Sulawesi.Methods of data analysis used were descriptive statistics and multiple linear regression analysis. Samples used in the study were 99 respondents, which were staff at the Board of Social Empowerment and Rural Government of Southeast Sulawesi.The results of the study showed that (1) There was a positive, significant effect of individual characteristics (X1) and career development (X2) on the performance of staff at the Board of Social Empowerment and Rural Government of Southeast Sulawesi . (2) The individual characteristics (X1) had a positive, significant effect on the performance of staff at the Board of Social Empowerment and Rural Government of Southeast Sulawesi. (3) Career Development (X2) had a positive, significant effect on the performance of staff at the Board of Social Empowerment and Rural Government of Southeast Sulawesi.Keywords: individual characteristics, career development, staff performance